Image-guided LINAC radiosurgery in hypothalamic hamartomas - Romanelli, Pantaleo; Tuniz, Francesco; Fabbro, Sara; Beltramo, Giancarlo; Conti, Alfredo (Frontiers in Neurology, 2022)
Introduction Hypothalamic hamartomas (HH) are developmental malformations that are associated with mild to severe drug-refractory epilepsy. Stereotactic radiosurgery (SRS) is an emerging non-invasive option for the treatment of small and medium-sized HH, providing good seizure outcomes without neurological complications. Here, we report our experience treating HH with frameless LINAC SRS. Materials and methods We retrospectively collected clinical and neuroradiological data of ten subjects with HH-related epilepsy that underwent frameless image-guided SRS. Results All patients underwent single-fraction SRS using a mean prescribed dose of 16.27 Gy (range 16–18 Gy). The median prescription isodose was 79% (range 65–81 Gy). The mean target volume was 0.64 cc (range 0.26–1.16 cc). Eight patients experienced complete or near complete seizure freedom (Engel class I and II). Five patients achieved complete seizure control within 4 to 18 months after the treatment. Four patients achieved Engel class II outcome, with stable results. One patient had a reduction of seizure burden superior to 50% (Engel class III). One patient had no benefit at all (Engel class IV) and refused further treatments. Overall, at the last follow-up, three patients experience class I, five class II, one class III and one class IV outcome. No neurological complications were reported. Conclusions Frameless LINAC SRS provides good seizure and long-term neuropsychosocial outcome, without the risks of neurological complications inherently associated with microsurgical resection.